Perceived Influences of Leadership on the Survival of Small and Medium Enterprises (SMEs) in Phnom Penh, Cambodia - Saroeum Kong; Sarom Mok; Songheang Ai (Universitas Majalengka, 2026)
Poor leadership practices by managers and business owners contributed to SMEs’ demise. This qualitative, descriptive case study examined how leadership affects SMEs’ ability to survive. The study looked into how leadership affects SMEs' ability to survive in Phnom Penh, Cambodia. The viewpoints and experiences of SME owners and managers provide insights into leadership strategies that help SMEs survive. The interview questions were answered by the twenty participants. Interviews, scheduling, obtaining consent papers, digitally capturing audio, and transcribing participant responses comprised the process. Data analysis was a continuous process that helped provide an analysis that addressed the study questions, which aided in understanding responses and coming to the right findings. The themes were coded with the help of Nvivo 10® data analysis software. The themes were identified during the preliminary data analysis and categorized based on typical responses. The results showed that there were four primary themes: the perspectives of leadership experience, leadership practices, business practices, and sustainable leadership practices on the survival of SMEs. It was recommended that SME owners identify and put into practice the organization’s fundamental values, which include work-life balance, integrity, customer focus, valued employees, trust, and creativity and innovation. Because a SME owner may interact with staff members more frequently and directly, their actions can have a big impact on the business. Leaders were advised to foster a culture of cooperation between the public, corporate, and academic sectors.